2014
DOI: 10.1589/jpts.26.1055
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lower Extremity Angle According to Heel-height Changes in Young Ladies in Their 20s during Gait

Abstract: [Purpose] The purpose of this study was to compare the effects of heel-height changes on the low joint angles of the lower extremities of women in their 20s during gait. [Subjects and Methods] Qualisys Track Manager Software ver. 2.8 (Qualisys, Sweden) was used to perform measurements on 14 female university students in their 20s. To measure movements, the subjects were asked to walk while wearing high-heeled shoes and reflective stickers on their hip joints, knee joints, and ankle joints, the changes in joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Owing to their soft and viscoelastic characteristics, insole, heel pad, and wedge of the shoe can effectively cushion the contact loading and reduce heel pressure at initial contact [ 12 , 13 ]. Additionally, according to earlier studies, these accessories of traditional shoes tend to shift the walker's center of mass (COM) anteriorly during walking [ 14 16 ], and in the present study, we notice that neutral running shoe walking tends to alleviate joint movement at the knee and ankle level. These effects may in turn alter limb alignment at heel landing, which is closely related to load and pressure distribution [ 17 , 18 ], and herein help to dissipate the landing load further [ 19 ].…”
Section: Discussionsupporting
confidence: 76%
“…Owing to their soft and viscoelastic characteristics, insole, heel pad, and wedge of the shoe can effectively cushion the contact loading and reduce heel pressure at initial contact [ 12 , 13 ]. Additionally, according to earlier studies, these accessories of traditional shoes tend to shift the walker's center of mass (COM) anteriorly during walking [ 14 16 ], and in the present study, we notice that neutral running shoe walking tends to alleviate joint movement at the knee and ankle level. These effects may in turn alter limb alignment at heel landing, which is closely related to load and pressure distribution [ 17 , 18 ], and herein help to dissipate the landing load further [ 19 ].…”
Section: Discussionsupporting
confidence: 76%
“…Our findings are comparable to previous reports of the effect of high heels in increasing the amplitude and area of sway during static standing4 ) and reduced dynamic stability during fore-aft walking22 ) . Similar negative effects of high heels on sensory input were identified by a reduction in two-point discrimination and sensitivity to light tactile touch on the soles of the feet, and lower position sense of the great toe in young females who wore high heels for more than 20 h per week13 ) . Other studies have reported a decrease in knee joint position sense following high-intensity isokinetic knee exercises26 ) .…”
Section: Discussionmentioning
confidence: 70%
“…The chronic demand on lower limb muscles and soft tissues to manage these changes in proprioception and base of support can eventually lead to inefficient contraction of leg muscles and abnormal muscle lengths12 ) . However, the effects of high heels on muscle activity, proprioception, and lower limb alignment have only been evaluated within the context of standing4, 13 ) , without consideration of the potentiating effects of walking in high heels. Therefore, the aim of our study was to examine the effects of increased heel height and gait velocity on balance control and knee joint position sense.…”
Section: Introductionmentioning
confidence: 99%
“…It's also a known fact that increasing heel heights increases the neck protrusion angle and the total body postural alignment changes leads to musculoskeletal problems. During gait cycle, the movements of the lower extremities were reduced with increase in heel height in women in 20's [17][18][19][20][21][22][23][24] . The subjects in this study using heels had more foot pain than subjects using flat footwear's due to the malalignment of foot structures.…”
Section: Discussionmentioning
confidence: 99%